Language and family entrepreneurship: empirical research based on micro survey data of CFPS in China - Chenglin Ren; Yijia Tang (PLoS ONE, 2025)
Language serves as a vital link between individuals. In a multi-ethnic country like China, significant differences exist between Standard Mandarin and various regional dialects, which can influence family entrepreneurs’ access to entrepreneurial resources and information. This paper examines the theoretical and empirical impact of Standard Mandarin and dialects on family entrepreneurship choice and performance, using microdata from the China Family Panel Studies (CFPS). The results show that families who predominantly use Standard Mandarin have a higher probability of starting a business, with cognitive competence and social networks as two important channels through which language influences the likelihood of entrepreneurship. Specifically, the effect of Standard Mandarin on urban families’ entrepreneurship choice is more significant, whereas the impact on rural families is not as pronounced. Regardless of whether they are in urban or rural areas, speaking a dialect is more beneficial for entrepreneurial families in terms of integrating into the local community, leading to better entrepreneurial performance. Further analysis reveals that in most of the ten dialect regions of China, Standard Mandarin has a significant positive impact on family entrepreneurship choice, but a significant negative impact on family entrepreneurial performance. In high-income, young, eastern, and central region families, the probability of starting businesses is higher for families using Standard Mandarin, while dialects have a significant positive impact on family entrepreneurial performance in most sub-samples.